2014
DOI: 10.1002/hec.3139
|View full text |Cite
|
Sign up to set email alerts
|

Welfare Reform and Children's Health

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 49 publications
(72 reference statements)
0
6
0
Order By: Relevance
“… 2. In contrast, scholars have explored more extensively whether the income support offered by other welfare programs has improved health. See, for example, Currie and Cole (1993), Bitler, Gelbach, and Hoynes (2005), Dunifon, Hynes, and Peters (2006), Milligan and Stabile (2011), Corman et al (2013), and Baltagi and Yen (2016). …”
mentioning
confidence: 99%
“… 2. In contrast, scholars have explored more extensively whether the income support offered by other welfare programs has improved health. See, for example, Currie and Cole (1993), Bitler, Gelbach, and Hoynes (2005), Dunifon, Hynes, and Peters (2006), Milligan and Stabile (2011), Corman et al (2013), and Baltagi and Yen (2016). …”
mentioning
confidence: 99%
“…Using data from the Survey of Income and Program Participation over the period 1994 to 2005, Baltagi and Yen examined the implementation of TANF policies (e.g., time limits, work requirements) on child health status, doctor consultations and nights of hospital stays as reported by parents of children under age 18 years in families where parents have at most a high school degree (Baltagi & Yen, 2014). Overall, the authors found that implementation of TANF was not related to child health status or doctor consultations, but was associated with an increase of 0.31 nights spent in the hospital.…”
Section: Effects Of Economic Security Policies On Healthmentioning
confidence: 99%
“…6 6. A large body of studies on TANF use the SIPP data set, and many of these drop the five states from their analysis (see Bavier 2002;Baltagi and Yen 2014;Herbst 2010;Mazzolari and Ragusa 2012;Ratcliffe et al 2008;Shaefer, Grogan, and Pollack 2011;Wallace 2009). For all analyses, I use individual weight, which is measured at the last wave during the panel.…”
Section: A Data: Survey Of Income and Program Participationmentioning
confidence: 99%
“…A large body of studies on TANF use the SIPP data set, and many of these drop the five states from their analysis (see Bavier ; Baltagi and Yen ; Herbst ; Mazzolari and Ragusa ; Ratcliffe et al ; Shaefer, Grogan, and Pollack ; Wallace ).…”
mentioning
confidence: 99%